2022
DOI: 10.1111/tbed.14706
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Sarcoptes scabiei provide new insights into adaptation to permanent parasitism and within‐host species divergence

Abstract: Sarcoptes scabiei is the causative agent of a highly contagious skin disease in humans and more than 100 mammals. Here, we reported the first chromosome‐level reference genome of S. scabiei isolated from rabbits, with a contig N50 size of 5.92 Mb, a total assembled length of 57.30 Mb, ∼12.65% repetitive sequences and 9333 predicted protein‐coding genes. The phylogenetic tree based on 1338 shared high‐confidence single‐copy orthologous genes estimated that the mammalian ectoparasite S. scabiei and the plant‐fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 146 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…Therefore, we speculate that different or altered cofactors in T. urticae led to changes in Hox gene function, as previous studies have shown that mite genomes are much smaller than those of other arthropods [ 35 ] and that Hox genes deletion varies among different mites [ 36 , 37 , 38 ]. In this regard, it has been suggested that Abdominal-A ( Abd-A ) was responsible for the morphological diversity of mites [ 39 ]. In addition, the relationship between Hox genes and the target gene ( DlI ) differed significantly in different arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that different or altered cofactors in T. urticae led to changes in Hox gene function, as previous studies have shown that mite genomes are much smaller than those of other arthropods [ 35 ] and that Hox genes deletion varies among different mites [ 36 , 37 , 38 ]. In this regard, it has been suggested that Abdominal-A ( Abd-A ) was responsible for the morphological diversity of mites [ 39 ]. In addition, the relationship between Hox genes and the target gene ( DlI ) differed significantly in different arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…felis of S. scabiei may not exist. This conclusion needs confirmation by further molecular analyses based, in parallel, on microsatellite markers and innovative genomic techniques [ 9 , 18 , 22 , 46 ]. A larger dataset of mites from diversified geographical areas and carnivore communities is similarly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the continued use of the term “var” in the past scientific literature referring to Sarcoptes host-specific subspecies or “strains” may be outdated or even misleading, appearing of little relevance. Accordingly, we believe that the contemporary understanding of the broad and sometimes unexpected host associations of S. scabiei should cautiously lead to the dismission of the historic nomenclature based on questionable mite morphological differences and the exclusive view of strict host association [ 46 ].…”
Section: Discussionmentioning
confidence: 99%